KEHILANGAN TANAH SAAT PANEN PADA TANAMAN BAWANG DAUN (Allium fistulosum L) - Nehemia Angeli Mukuan; Yani E. B. Kamagi; Jooudie N. Luntungan (COCOS, 2020)
ABSTARCT The purpose of this study was to determine the amount of soil transported or involved in the roots and stems of leeks at harvest time. This research was conducted to determine the amount of soil involved when the leek plants were harvested in the agricultural land of Rurukan, East Tomohon sub-district. This plant is a potential commodity and important for the local community because it supports the economy of the farming community. This research uses descriptive research methods (Anonymous, 1984). The variables observed were root weight (Xa) and leek stem diameter (Xb) to the amount of soil transported (Yt) with a total of 40 samples with the multiple linear regression analysis method at the 5% level (Sugiarto, 1992). The results showed that the amount of soil transported on one leeks plants was 4.1064 gr with an estimated value based on multiole regression equation, namely: Yt = 0.3253 + 3.2661Xa + 0.5150Xb, at R2 = 0.6292. Key words: Loss of Soil, Leek